METHODS FOR SOLVING A SYSTEM OF EQUATIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article is devoted to studying the didactic and practical possibilities of using the cluster method in solving systems of algebraic equations. The study analyzes the impact of cluster learning technology on the systematization of educational material, the clear reflection of logical connections between concepts, and the deep and conscious assimilation of the subject by students. The importance of the cluster method combined with mathematical modeling in improving the effectiveness of education and the advantages of using it to teach systems of linear equations based on the Cramer, matrix, and Gauss methods are also highlighted. This article is devoted to considering the main possibilities of using the cluster method in methods for solving a system of linear algebraic equations. Particular attention is paid to increased educational efficiency with mathematical modeling based on the cluster method of teaching.